Invasão biológica e manejo da goiabeira (Psidium guajava L.) na sucessão inicial em pastagens abandonadas na planície de inundação do alto rio Paraná. - Chapla, Tatiani Elisa (2014)
Changes in land use can promote the colonization of naturally susceptible environments, such as riparian zones, by invasive alien species, which can delay or prevent the processes of forest regeneration. These species often create conditions that facilitate their persistence and hinder the recovery of the original ecosystem. I present here two papers on the evaluation of 1) the impact of Psidium guajava L. dominance in secondary succession of abandoned pastures in the upper Paraná River-floodplain (UPRF); and 2) the impact of P. guajava clearing on native vegetation recovery in the same sites. In the first paper I compared the tree seedling banks of sites dominated by the exotic P. guajava and sites dominated by native species. In the second paper I evaluated the recruitment of native trees in response to three treatments: cutting all P. guajava individuals + herbicide; cutting all P. guajava individuals; and no action (control). The tree seedling bank in the area dominated by P. guajava had higher density, but lower species richness than in the area with dominance of natives. Species composition also differed between areas. P. guajava clearing led to an increase in trees' density and saplings' diversity, while the seedling bank showed almost no response to treatments. These results indicate that P. guajava control was effective in stimulating the recruitment of native trees. However, without continuous management P. guajava may reestablish and become dominant again. If P. guajava dominance in early succession is let without intervention, the abandoned pastures at the UPRF may turn into forests with low diversity and unrepresentative of the regional biodiversity. Management projects should be designed with an ecosystem scale approach, in which medium and long-term monitoring would certainly be required.